Development of a Basic Digital Skills Assessment System for Employees - มีหอม, สิทธิพงษ์; นกกาศักดิ์, วรรณธิชา; แก้วกระจ่าง, ณัฏฐณิชา; นาคสุข, พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, entitled “Development of a Digital Skills Assessment System for Employees” is a developmental research study. The objectives of this research were: 1) to develop a digital skills assessment system for employees, and 2) to evaluate the efficiency of the developed system. The sample group consisted of 30 employees working in organizations that utilize digital technology in their operations, selected through purposive sampling based on criteria aligned with the research objectives. Additionally, three experts were involved in evaluating the system efficiency. The research instruments included: 1) a digital skills assessment system for employees, and 2) to evaluate the efficiency of the developed system in terms of system performance, usability, and accuracy of assessment results; and 3) to examine user satisfaction with the system.            The results indicated that the developed digital skills assessment system achieved the highest level of efficiency, as evaluated by three experts, with a mean score (x̄) of 4.53 and a standard deviation (S.D.) of 0.54. Furthermore, the satisfaction of the sample group, consisting of 30 employees selected through purposive sampling, was at a highest level, with a mean score (x̄) of 4.83 and a standard deviation (S.D.) of 0.35. It can be concluded that the developed system is highest level and appropriate for practical implementation in assessing employees’ basic digital skills. Moreover, it can be effectively utilized as a tool to support organizational workforce development planning.